Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Produk Telekomsel Di Kabupaten Karawang - Villy, Villy; Kusmayadi, Odang (Peneliti.net, 2023)
This study aims to examine and analyze product quality and promotion on purchasing decisions for Telkomsel products in Karawang regency. The survey in this study was conducted at the Grapari Outlet, Karawang Regency. The data used in this study is primary data obtained from the results of distributing questionnaires to Telkomsel provider users. The method used in this research is quantitative with a descriptive and verification approach. The samples used were 375 samples and 5,987 populations which were taken using the nonprobability sampling method with the accidental sampling technique. The analysis technique used in this study is Scale Range Analysis and Path Analysis using the Succesive Interval Method (MSI) and SPSS 26 Software. The results of the research that has been conducted show that partially product quality has a significant effect on purchasing decisions, promotion has a significant effect on Purchasing Decisions. Simultaneously Product Quality and Promotion affect Purchase Decisions